Water-Soluble Vitamin Levels and Supplementation in Chronic Online Hemodiafiltration Patients - Schwotzer, Nora (Kidney Int Rep, 2020)
INTRODUCTION: Supplementation of water-soluble vitamins is a common practice in hemodialysis patients, but dosages are largely based on conventional hemodialysis techniques. The aim of this study was to assess the status of water-soluble vitamins in patients on hemodiafiltration (HDF), and attempt to determine optimal dose of vitamin supplements. METHODS: This monocentric study included 40 patients on thrice-weekly chronic HDF. At baseline, all patients received 2 tablets of Dialvit containing B and C vitamins after each dialysis session. Predialysis samples of B and C vitamins were measured in both blood (n = 40) and a subgroup of dialysate (n = 6) samples. A second blood sample was obtained in 24 patients 3 months after dose adjustment of the vitamin supplement. RESULTS: At baseline, B-vitamin levels were high with, respectively, 0.4%, 10.0%, and 89.6% of patients in the low, normal, and high reference range. For vitamin C, most patients were in the normal range (5.0%, 82.5%, and 12.5% in low, normal, and high reference range). Three months after dose reduction, B vitamin levels decreased but stayed mostly at or above the normal range (1.4%, 25.7%, 72.9% in low, normal, and high reference range). Three patients (12.5%) developed vitamin C deficiency on low-dose substititon. CONCLUSION: This study shows that the levels of most vitamins are above the normal range in patients on HDF receiving a classic dose of vitamin supplements, vitamin C excepted. Our study suggests that the classic dose of postdialysis vitamin B supplements may be reduced.